Growth and Yield Attributres of Tomato (Solanum Lycoperscicum L.) Influenced by Different Mulches and Levels of Irrigation in Northern Dry Zone of Karnataka - Raut, Namita (Annals of Arid Zone, 2025)
An experiment was carried at College of Horticulture, Bagalkote to study the effect of different mulches and levels of irrigation on growth and yield attributes of tomato. The study was carried out with 12 treatment combinations and replicatedthrice in split plot design. The main plots were assigned four irrigation levels based on cumulative pan evaporation: I1: 100%, I2: 80%, I3: 60%, and I4: 40%. The subplots consisted of three mulching treatments: M1: no mulch, M2: sugarcanemulch, and M3: polythene mulch. Irrigation was given based on cumulative pan evaporation (CPE) following alternate day irrigation schedule using drip. The treatment combination (I2M3) comprising drip irrigation at 80% CPE in combination of polythene mulch recorded highest plant height (112.1 cm), maximum number of branches plant-1 (16.0) and maximum plant canopy in East-West (112.5 cm) and North-South (111.8 cm) directions. Total yield (51.8 t ha-1) and other yield attributing characters like flowers number cluster-1 (7.23), fruits cluster-1 (6.1), average weight of the fruit (63.4 g), fruit yield plant-1 (2.7 kg) were also high under this treatment.